First report of hard shell female mating in the crenate swimming crab, Thalamita crenata Ruppell, 1830 (Crustacea: Decapoda: Portunidae) - Lirong Yu, Abit; Julia Hwei Zhong, Moh; Jongkar, Grinang; Wan Zabidii, Wan Morni; Abdulla, Al-Asif; Kamil, Latif (Genesis Publishing Consortium Limited, 2024)
The mating behaviour of crustaceans, particularly brachyuran crabs, is commonly associated with the female molting cycle, with soft shell mating prevalent among sexually reproducing species, while hard shell mating is a rarely observed adaptation within the subfamily Thalamitinae. This study marks the initial documentation of hard shell female mating in Thalamita crenata, a portunid crab. The study aims to elucidate the reproductive dynamics of T. crenata by capturing and observing mating behaviours in captivity. Mature T. crenata individuals of both sexes were captured and housed in controlled conditions. Observations were conducted to document hard shell mating behaviours, employing digital video and photography for detailed analysis. After 50 days, a notable instance of hard shell mating was observed, characterized by forceful gripping and flipping manoeuvres by the male, culminating in copulation lasting approximately 8 minutes. This discovery enriches our understanding of T. crenata's reproductive ecology, providing insights into unique mating strategies within the subfamily Thalamitinae. This discovery encourages further exploration of captive breeding possibilities and contributes to a holistic comprehension of crustacean mating strategies.